APPLYING THE CORRECT TOURISM VOCABULARIES AS A FORM OF GUIDE’S POLITENESS STRATEGY TOWARD JAPANESE VISITOR - A.A.Ayu Dian Andriyani; Ni Wayan Meidariani (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2016)
The use of the correct Japanese tourism vocabularies by guide when giving service to visitors is as one of form of politeness. This study describes many parts of speech in Japanese tourism vocabularies and politeness strategy used by guide when touring around tourism object in Bali.Theory which is used is Brown and Levinson politeness theory supported by Goi classifying theory and politeness theory and context which gives effect to content and form of guide’s communication when interacting with Japanese visitors. This qualitative research uses non-participant observation method by listening technique and makes a note by analyzing technique which is pragmatic equivalence. Result of the study shows that vocabularies of Japanese tourism use parts of speech which consist of verb, noun, adjective, which are spoken based on speaking situation context which follows it so that the correct vocabulary usage is as a form of politeness strategy of guide in giving service toward Japanese visitors. Moreover, guide has applied both negative and positive politeness strategy as service to JV based on situation context.